Relationship Analysis of Eco-Control, Company Age, Company Size, Carbon Emission Disclosure, and Economic Consequences - Ambarwati Ambarwati; Dody - Hapsoro; Crescentiano Agung Wicaksono (The Indonesian Journal of Accounting Research, 2020)
The purpose of this study is to examine the effect of eco-control on carbon emission disclosure and to examine the effect of carbon emission disclosure on economic consequences. Companies used as samples are oil, gas and coal companies in in non-Annex 1 member countries which data are available in the Osiris database. The observation period begins at the commencement of Kyoto Protocol commitment to date or from 2013 to 2016. Data analysis technique used in this research is Partial Least Square method using WarpPLS 4.0 application. Test results show that eco-control positively affects carbon emissions disclosure. Furthermore, carbon emissions disclosure positively affects trading volume and negatively affects bid-ask spread and share price volatility. This study has implications for governments and companies. Governments can change the rules to make carbon emission disclosure as mandatory disclosure for companies that have the potential to generate carbon emissions. Companies that have environmental concerns and disclose carbon emissions will gain legitimacy and a positive response from stakeholders.